Study protocol for the systematic review and meta-analyses of the association between schizophrenia and bone fragility. Issue 12 (12th December 2020) - Azimi Manavi, Behnaz; Stuart, Amanda L; Pasco, Julie A; Hodge, Jason M; Corney, Kayla; Berk, Michael; Williams, Lana J
Abstract : Introduction: Individuals with schizophrenia are known to be at higher risk of comorbid conditions, both physical and psychological. Osteoporosis is possibly one of these, leading to public health concerns due to higher rates of associated mortality and morbidity. We aim to systematically search all available evidence across electronic databases regarding the relationship between schizophrenia and bone fragility. Methods and analysis: A systematic search of the research databases CINAHL, MEDLINE Complete, Embase and PsycINFO will be conducted and identified papers reviewed for eligibility, with a second reviewer confirming inclusions. Searches will be run from database inception to 1 October 2020 and supplemented by the hand checking of references of identified articles. A previously published scoring system will be used for assessing the methodological quality and risk of bias. A meta-analysis is planned. Ethics and dissemination: Due to including published literature only, ethical permission will not be necessary. Results of this study will be published in a relevant scientific journal and presented at a conference in the field of interest. PROSPERO registration number: CRD42020171959.